2012
DOI: 10.3158/2158-5520-5.1.40
|View full text |Cite
|
Sign up to set email alerts
|

The Roots of Amphibian Morphospace: A Geometric Morphometric Analysis of Paleozoic Temnospondyls

Abstract: Temnospondyls-a major component of Permian and Carboniferous terrestrial ecosystems-display great diversity in skull shapes and proportions. To quantify and interpret this diversity, we conducted a geometric morphometric analysis using 45 landmarks on the dorsal skull surface of 90 species with well-represented cranial material. Results show a correlation between morphospace occupation and phylogenetic proximity of taxa for trees in which dvinosaurs and dissorophoids are sister groups and join an edopoid--eryo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 82 publications
(129 reference statements)
0
21
0
Order By: Relevance
“…The pattern for extant caecilian cranial shape of discontinuous morphospace occupation with distinct, clumped monophyletic groups contrasts with the findings from large-scale morphometric studies of other taxa, which have found species to be more evenly dispersed in shape space, often with overlapping clades (Neige 2003;Stayton 2005;Clabaut et al 2007;Cooper et al 2010;Drake and Klingenberg 2010;Friedman 2010;Monteiro and Nogueira 2011;Angielczyk and Ruta 2012;Prevosti et al 2012;Sallan and Friedman 2012;Klingenberg and Marugán-Lobón 2013). Instances of discontinuous morphospace occupation in other taxa are largely restricted to the most distinct, morphologically outlying clades, as is the case for cetaceans among mammals (Marcus et al 2000), gharials among crocodilians (Pierce et al 2008), and oviraptorosaurs among therapod dinosaurs (Brusatte et al 2012).…”
Section: History Of Morphological Diversificationmentioning
confidence: 52%
See 2 more Smart Citations
“…The pattern for extant caecilian cranial shape of discontinuous morphospace occupation with distinct, clumped monophyletic groups contrasts with the findings from large-scale morphometric studies of other taxa, which have found species to be more evenly dispersed in shape space, often with overlapping clades (Neige 2003;Stayton 2005;Clabaut et al 2007;Cooper et al 2010;Drake and Klingenberg 2010;Friedman 2010;Monteiro and Nogueira 2011;Angielczyk and Ruta 2012;Prevosti et al 2012;Sallan and Friedman 2012;Klingenberg and Marugán-Lobón 2013). Instances of discontinuous morphospace occupation in other taxa are largely restricted to the most distinct, morphologically outlying clades, as is the case for cetaceans among mammals (Marcus et al 2000), gharials among crocodilians (Pierce et al 2008), and oviraptorosaurs among therapod dinosaurs (Brusatte et al 2012).…”
Section: History Of Morphological Diversificationmentioning
confidence: 52%
“…However, some caution is necessary because discontinuity may be caused by sampling artefacts, such as the marked discontinuity found in a study of mammal skulls that included species from two distinct clades, carnivores and marsupials, each of which were continuously distributed in the morphospace (Wroe and Milne 2007; note that mandible shape appears to be more continuously distributed, Prevosti et al 2012). Morphometric studies of skull shape in fossil temnospondyls, tetrapods probably more closely related to caecilians and other modern amphibians than to any other living vertebrates, also show mostly evenly dispersed taxa in shape space with a modest degree of clustering of phylogenetic groups and considerable overlap between them (Stayton and Ruta 2006;Fortuny et al 2011;Angielczyk and Ruta 2012). Judged against the available comparative empirical studies, the starburst pattern with very distinct clusters corresponding to main clades appears to be an unusual feature of caecilian crania.…”
Section: History Of Morphological Diversificationmentioning
confidence: 93%
See 1 more Smart Citation
“…Temnospondyls display a diverse range of cranial shapes (Angielczyk & Ruta, ), and studies on the shapes and mechanics of temnospondyl skulls have interpreted cranial shape as reflecting diet and prey capture techniques (Fortuny, Marcé‐Nogué, De Esteban‐Trivigno, Gil, & Galobart, ; Fortuny, Marcé‐Nogué, Gil, & Galobart, ). In spite of this, temnospondyls have historically been treated very coarsely in paleoecological analyses, with overall body size used as the only ecologically relevant variable for distinguishing species (e.g., Benton, Tverdokhlebov, & Surkov, ; Roopnarine et al, ; Roopnarine & Angielczyk, ; Tarailo & Fastovsky, ).…”
Section: Introductionmentioning
confidence: 99%
“…Throughout their evolutionary history, temnospondyls displayed a large variety of skull shapes, ranging from dorsoventrally flattened (platyrostral) and compact forms to long-snouted and mediolaterally narrow skulls (Angielczyk and Ruta 2012), providing evidence for the morphological diversity of the cranial skeleton among this group. The large disparity regarding cranial features, such as orbit and interpterygoid vacuity size, appears to reflect this overall pattern of cranial evolution.…”
Section: Discussionmentioning
confidence: 99%